The significance of benzo[b]naphtho[d]furans in fluids and source rocks: New indicators of facies type in fluvial-deltaic systems - Cesar, J.; Grice, Kliti (Pergamon, 2017)
© 2017 Elsevier Ltd The distributions of benzo[b]naphtho[d] furans (BNFs) in source rocks and fluids (crude oil and condensate) are shown to be useful indicators of facies type in fluvial-deltaic systems from the Dampier sub-Basin, North West Shelf of Australia. The stratigraphy in the Dampier sub-Basin represents a challenging petroleum system where the organic matter is very similar in most of the Triassic-Jurassic sequences. These sections consist of a fluvial-deltaic system with increasing marine influence towards the end of the Jurassic period. Potential applications of BNFs for source rock characterisation as well as fluid – source rock correlations are reported for the first time. The formation of [1,2]BNF seems to be influenced by clay catalysis, and the ratio [2,1] /[1,2]BNF can be used to describe lithofacies. This ratio is much lower in sediments from fluvial-deltaic systems compared to clay-depleted sediments from marine environments (e.g. carbonate sequences). For this study, the Triassic source rocks show ratios of 0.9–1.5 with 25% w/w of clay content in the rock whereas the ratios for the Middle Jurassic source rocks are around 1.6–2.1 with 14% w/w of clay content. The BNF ratio is lowest in the Late Jurassic samples (0.8) with 28% w/w of clay minerals. The ternary plot of [2,1] -[1,2]-[2,3] BNFs could be applied to fluid–fluid and fluid-source rock correlations. However, further work needs to be done on the factors controlling the abundance of the [2,3]BNF which is more abundant in source rocks compared to the fluids generated and expelled from these.